O10.4 Performance of self-collected penile swabs for the detection of chlamydia trachomatis, neisseria gonorrhoeae, trichomonas vaginalis, and mycoplasma genitalium. (13th September 2015) - Gaydos, CA; Dize, L; Barnes, M; Barnes, P; Hsieh, Y-H; Duncan, D; Marsiglia, V
Abstract : Introduction: Urethral swabs are used for culture of gonorrhoea (NG) in males and for detection of chlamydia (CT) and NG by nucleic acid amplification tests (NAATs). We hypothesised self-collected penile swabs would perform as well as urethral swabs for detection of CT, NG, trichomonas (TV) and mycoplasma (MG). Methods: Men having urethral swabs obtained for NG culture in the STD clinic volunteered to collect penile swabs. Urethral swabs were placed into NAAT transport media; then self-collected penile swabs were placed in transport media. NAATs were performed for CT, NG, TV, and MG for urethral and penile swabs. Acceptability questionnaires were given. Results: For 203 urethral/penile pairs, there were 32 penile positive for CT (15.8%), 31 urethral positive for CT (15.3%); [sensitivity 96.8% and specificity 98.8% compared to urethral swabs]. There were 29 penile positives for NG (14.3%) and 27 urethral positives for NG (13.3%); [sensitivity 100%, specificity 98.9%]. 25 were Gram stain positive; 21 by culture. For TV, there were 23 penile positives (11.3%), 20 urethral positives (9.9%); [sensitivity 85.0%, specificity 96.7%]. For MG, 24 penile swabs were positive (11.8%); and 29 urethral were positive (14.3%); [sensitivity 79.3%, specificity 99.4%]. CT: 2 samples were penile+/urethral-, 1 was penile-/urethral+. NG: 2 samples were penile+/urethral-. TV: 6 samples were penile+/urethral-, 3 were penile-/urethral+. MG: 1 pair was penile+/urethral-, 6 were penile-/urethral+. There were no significant differences between self-collected penile swabs and clinician-collected urethral swabs for NAATs (p = 0.625 for CT; p = 0.248 for NG; p = 0.344 for TV; and P = 0.070 for MG). 100% of men preferred penile swabs for diagnosis. Conclusions: Self-collected penile swabs were as accurate as urethral swabs for the detection of sexually transmitted infections for NAAT assays and could expedite express visits in a busy STD clinic. Penile swabs show promise as a method of utilising one sample for multiple STIs. Disclosure of interest statement: The research group has previously received research funding from GenProbe/Hologic. No pharmaceutical grants were received in the development of this study.